2001
DOI: 10.1021/ol016542i
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nucleophilic Substitution of in Situ Generated 3-tert-Butyldimethyl- silyloxyalk-2-enylsulfonium Salts with Allylindium Reagents

Abstract: [reaction: see text] In situ generated 3-tert-butyldimethylsilyloxyalk-2-enylsulfonium salts derived from the reaction of alpha,beta-enones with dimethyl sulfide in the presence of TBSOTf undergo a novel nucleophilic substitution with in situ generated allylindium reagents from indium and allyl halides to give silyl enol ethers of delta,epsilon-unsaturated ketones, which correspond to Michael addition products, in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…One reason for this scarcity is the lack of a good and simple method for the preparation of the requisite substrates. Therefore development of a concise method for the direct 1,4-propargylation onto α,β-unsaturated ketones with simultaneous silylation of the produced enolates is highly desirable. , Recently, we reported that 3- tert -butyldimethylsiloxyalk-2-enylsulfonium salts generated in situ by the reaction of α,β-unsaturated ketones with tert -butyldimethylsilyl triflate and dimethyl sulfide undergo 1,4-allylation with allylindium reagents to afford the corresponding 1,4-allylated silyl enol ethers (formal 1,4-addition onto α,β-unsaturated ketones) in good yields . We thought of applying this protocol for the preparation of 6-siloxy-5-en-1-yne derivatives using propargyl bromide instead of allyl bromide …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this scarcity is the lack of a good and simple method for the preparation of the requisite substrates. Therefore development of a concise method for the direct 1,4-propargylation onto α,β-unsaturated ketones with simultaneous silylation of the produced enolates is highly desirable. , Recently, we reported that 3- tert -butyldimethylsiloxyalk-2-enylsulfonium salts generated in situ by the reaction of α,β-unsaturated ketones with tert -butyldimethylsilyl triflate and dimethyl sulfide undergo 1,4-allylation with allylindium reagents to afford the corresponding 1,4-allylated silyl enol ethers (formal 1,4-addition onto α,β-unsaturated ketones) in good yields . We thought of applying this protocol for the preparation of 6-siloxy-5-en-1-yne derivatives using propargyl bromide instead of allyl bromide …”
mentioning
confidence: 99%
“…To a THF solution of cyclohex-2-en-1-one 1a were added t -butyldimethylsilyl triflate and dimethyl sulfide successively to afford in situ 3- tert- butyldimethylsiloxycyclohex-2-enylsulfonium salt, which was treated at −78 °C with organoindium reagent generated in situ from indium-metal and propargyl bromide in THF at room temperature . Gratifyingly, usual workup of the reaction mixture gave the desired silyl enol ether 2a in 76% yield.…”
mentioning
confidence: 99%
“…The general scheme (Scheme 151) applies to both cyclic and acyclic systems. The chemistry of arsenic (e.g., using AsPh 3 ) 272 and sulfur (e.g., using Me 2 S) 273 adducts is being developed along similar lines.…”
Section: Umpolung-halogenationmentioning
confidence: 99%
“…In the first place, allenylation in the presence of silyl triflate and dimethyl sulfide was examined . As it is known that indium reagents prepared from propargyl bromides having a substituent on the terminal alkyne react with aldehydes or ketones to give allenyl compounds as the major product, we expected that 1,4-allenylsilylation could be achieved by employing indium reagents prepared from substituted propargyl bromides and indium metal.…”
mentioning
confidence: 99%